Perbedaan Cardiothorax’s Ratio Foto Rontgen Polos Usia di Atas 50 dan di Bawah 50 Tahun pada Pasien Diabetes Melitus di RS Royal Prima Jambi - Leo Nardi (Universitas Adiwangsa Jambi, 2024)
Background: The cardiothoracic ratio (CTR) is a crucial radiological indicator used to assess cardiac size and detect cardiomegaly, particularly in patients with chronic diseases such as diabetes mellitus. Cardiovascular complications are common in diabetic patients and may progress with age. Evaluating CTR differences between age groups in diabetic populations can aid in early risk detection. Objective: To determine the differences in cardiothoracic ratio on chest X-rays between diabetic patients aged above 50 years and those aged 50 years and below at Royal Prima Hospital Jambi. Methods: This retrospective descriptive-comparative study utilized secondary data from chest X-rays of diabetic patients at Royal Prima Hospital Jambi. Subjects were divided into two age categories: ≤50 years and >50 years. The CTR was measured using the standard posteroanterior radiographic method and analyzed statistically to evaluate differences between groups. Results: The study found a statistically significant difference in CTR between the two age groups. Patients over 50 years old had a higher average CTR than those 50 years and below, suggesting an increased risk of cardiomegaly in older diabetic patients. Conclusion: There is a significant difference in cardiothoracic ratio between diabetic patients aged over 50 years and those aged 50 years and below. These findings indicate that age is a contributing factor in cardiac enlargement among diabetic patients, supporting the need for age-specific cardiovascular monitoring strategies.